2015
DOI: 10.5993/ajhb.39.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Discrimination among Minority College Students

Abstract: Understanding the predictors of perceived racial discrimination may allow for the development of interventions that alleviate the stress associated with discrimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
(69 reference statements)
1
8
0
Order By: Relevance
“…The trustworthiness of the study was ensured by the fact that a) all participants were encouraged to speak freely about their experiences; b) all the steps in the analysis [17] were strictly followed; c) three of the authors participated in the coding of the data and d) the students’ voices were heard and accounted for using quotations. Moreover, the findings were linked with those from other international studies [4, 1012, 18, 20], which bolsters the integrity of the current study. Thus, this study has demonstrated that participants experienced similar challenges as ethnic minority students’ in other western countries.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The trustworthiness of the study was ensured by the fact that a) all participants were encouraged to speak freely about their experiences; b) all the steps in the analysis [17] were strictly followed; c) three of the authors participated in the coding of the data and d) the students’ voices were heard and accounted for using quotations. Moreover, the findings were linked with those from other international studies [4, 1012, 18, 20], which bolsters the integrity of the current study. Thus, this study has demonstrated that participants experienced similar challenges as ethnic minority students’ in other western countries.…”
Section: Discussionsupporting
confidence: 81%
“…Learning a new language and different ways of academic writing is difficult and may affect or impede academic performance. Coupled with that, ethnic minority students also reported facing discrimination and maintaining their cultural identity [68, 10, 11]. Additionally, these particular students may also face a sense of belonging [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Countless studies have demonstrated that BIPOC students struggle with racial tension on college campuses and experience differential treatment and stereotyping (McClain et al, 2016). These experiences of discrimination also represent barriers to success for students of color in university settings (Banks, 2010; Hall et al, 2015) leading to minority status stress, which can increase feelings of isolation and heighten mental health stressors (Banks, 2010; McClain et al, 2016). Furthermore, both discrimination and negative perceptions of the campus racial climate impact psychological functioning, poor academic performance, imposter syndrome, and feelings of not belonging (Cokley et al, 2013).…”
Section: Discriminationmentioning
confidence: 99%
“…Regardless, the research is clear that the sociocultural experiences of those who are U.S.-born are distinct from immigrants and aggregate data is likely to mask not only prevalence but also obfuscate unique health risk factors associated with nativity (Miller, 2010). Racial discrimination is a frequent stressor experienced by Asian American college students and may have especially damaging consequences during this development period (Hall et al, 2015;Tran & Sangalang, 2016). Comprehensive reviews highlight the deleterious effects of racial discrimination on a wide range of health outcomes, including alcohol misuse, psychological distress, depression, and physical health problems (Pascoe & Smart Richman, 2009;Williams & Mohammed, 2009).…”
mentioning
confidence: 99%